A quasigroup-based public-key cryptosystem - Kościelny, Czesław; Mullen, Gary L. (Zielona Góra: Uniwersytet Zielonogórski)
A public-key cryptosystem, using generalized quasigroup-based streamciphers is presented. It is shown that such a cryptosystem allows one to transmit securely both a cryptogram and a secret portion of the enciphering key using the same insecure channel. The system is illustrated by means of a simple, but non-trivial, example.
Keywords: quasigroups; latin squares; cryptography; streamciphers